Impact of FDI on the Indian Retailing Industry - Khattar, Sugandha (2007)
This dissertation provides a detailed analysis of the impact of foreign direct investments on the Indian economy, specifically the retailing industry. The Indian retailing Industry has of late been recognized as one of the sunrise sectors in the economy, attracting a lot of foreign investments. With this research, I analyze the prospects of these foreign investors and the impact their investments would have on the Indian economy, the consumers and the retailing industry.